Antecedents of Citizen-Centric E-Government Adoption: A Systematic Literature Review and Future Research Agenda - Kazembe Kazembe; Obert Sifile; Gilbert Mahlangu (Journal of Information System and Informatics, 2026)
Although e-government adoption has been widely studied, limited attention has been given to citizen-centric adoption, despite citizens’ willingness being central to e-government success. This study systematically synthesises the literature to identify and conceptualise the multidimensional antecedents of citizen-centric e-government adoption. Following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, peer-reviewed studies published between 2004 and 2025 were retrieved from Scopus and Web of Science. A total of 87 studies were analysed to address four research questions. The review identifies 21 antecedents grouped into six dimensions: trust factors, technology acceptance constructs, system quality, user competency, enabling conditions, and security and privacy concerns. The Unified Theory of Acceptance and Use of Technology (UTAUT) emerged as the most frequently applied framework, followed by the Technology Acceptance Model (TAM). The findings show that citizen adoption is multidimensional and is best explained through integrated theoretical perspectives. The proposed taxonomy offers researchers a structured basis for empirical validation and provides policymakers with theory-informed guidance for improving adoption. Without addressing these interconnected antecedents, e-government may continue to operate alongside, rather than transform, traditional service delivery.